The effect of macroeconomic conditions on the capital structure adjustment speed of South African listed firms - Krishna, Sudha (My University, 2012)
This paper uses a two-stage, dynamic partial adjustment model which accounts for potential mean-reversion, with the Arellano-Bover GMM estimation technique, to observe the effect of various macroeconomic variables on the speed at which South African listed firms adjust toward their target capital structures. Employing two definitions of financial constraints, these effects were also compared for financially constrained and unconstrained subsamples. Using a sample of listed firms spanning from 2000 to 2010, the findings of the study show some indication that firms adjust faster in unfavourable macroeconomic states relative to favourable states. There is also evidence to suggest that the adjustment dynamics of unconstrained firms differ from that of constrained firms. In addition, higher adjustment speeds are generally observed when using short-term debt relative to other debt definitions. However, the evidence is largely inconclusive as adjustment speed estimates are highly sensitive to the definition of financial constraints used, and to the inclusion of extreme leverage observations.
Keywords: Corporations; Finance; Corporate debt; Capital